TEORI KRITIS DAN PENGETAHUAN INKLUSIF: KAJIAN DOUBLE CONSCIOUSNESS, SITUATED KNOWLEDGE, DAN REFLEKSIVITAS KRITIS - Ikhsan, M. Alifudin; Muzdalifah, Zahrotul; Anam, Faris Khoirul; Adzim, Abdul (YAYASAN PERCIKAN INSAN MANDIRI (PRISMA), 2024)
This research aims to explore the epistemological contribution of Critical Theory in developing a more inclusive and just understanding of knowledge. The main focus is to examine the ways in which concepts such as double consciousness, situated knowledge, and critical reflexivity can help overcome biases and limitations in established knowledge narratives and open up space for alternative voices. The research method used is a literature review by identifying, selecting, analysing, and synthesising literature sources relevant to this topic. The results show that the concept of double consciousness introduced by W.E.B Du Bois places an important emphasis on recognising plural perspectives in knowledge production, especially from marginalised groups. Furthermore, situated knowledge proposed by Donna Haraway offers a solution to overcome bias by emphasising that knowledge is always situated in a particular social, cultural and political context. Finally, critical reflexivity is seen as an important practice to uncover the ideological and political interests hidden behind established knowledge narratives. This research recommends the need for further investigation on how these concepts can be operationalised in research and educational practices to create a more inclusive and transformative epistemology. In addition, empirical investigations on the impact of applying these concepts are also needed to understand the challenges and opportunities in the effort to develop more equitable and diverse knowledge.